2012
DOI: 10.1371/journal.pone.0042529
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes of Gut Microbiota during Berberine-Mediated Prevention of Obesity and Insulin Resistance in High-Fat Diet-Fed Rats

Abstract: Berberine, a major pharmacological component of the Chinese herb Coptis chinensis, which was originally used to treat bacterial diarrhea, has recently been demonstrated to be clinically effective in alleviating type 2 diabetes. In this study, we revealed that berberine effectively prevented the development of obesity and insulin resistance in high-fat diet (HFD)-fed rats, which showed decreased food intake. Increases in the levels of serum lipopolysaccharide-binding protein, monocyte chemoattractant protein-1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
367
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 457 publications
(399 citation statements)
references
References 66 publications
30
367
1
1
Order By: Relevance
“…25 In agreement with a previous study, BBR actions were confirmed here in decreasing body weight, fasting blood glucose levels, HOMA-IR, and improving impaired glucose tolerance and insulin tolerance in diabetic mice. 26 BBR-SLNs at 100 mg/kg dosage showed more potent effects than the equivalent dose of BBR in db/db mice, especially in improving glucose tolerance and insulin sensitivity. In addition, BBR-SLNs increased the pancreatic islet numbers.…”
Section: Hypoglycemic Effect Of Bbr-slnmentioning
confidence: 89%
“…25 In agreement with a previous study, BBR actions were confirmed here in decreasing body weight, fasting blood glucose levels, HOMA-IR, and improving impaired glucose tolerance and insulin tolerance in diabetic mice. 26 BBR-SLNs at 100 mg/kg dosage showed more potent effects than the equivalent dose of BBR in db/db mice, especially in improving glucose tolerance and insulin sensitivity. In addition, BBR-SLNs increased the pancreatic islet numbers.…”
Section: Hypoglycemic Effect Of Bbr-slnmentioning
confidence: 89%
“…Because Berberine, as a strongly intestinal protector used widely in the treatment of enteritis, is insoluble and rarely absorbed in gastrointestinal tract, it is reasonable to suggest that it may improve diabetes through the modulation of intestinal microbiota and intestinal permeability. Zhang et al (2012) studied the alteration of gut microbiota before and after Berberine treatment, …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the leptin levels of rats fed a high-fructose diet should be higher, as compared with those in the control group. The present study demonstrated that high-fructose foods may lead to excessive insulin secretion, thereby stimulating the production of leptin (29,31). All L. rotatum flavonoids were able to downregulate leptin and, owing to their potential hypolipidemic effects, further studies investigating the flavonoids of various Mongolian medicines are recommended in the future.…”
Section: Discussionmentioning
confidence: 60%